33.6k views
3 votes
Solve
8- (2x - 9) = 17 - 2x
Nchey

User Chklang
by
4.5k points

2 Answers

2 votes

Equation: 8 - (2x - 9) = 17 - 2x

First, we distribute the - sign.

8 -2x + 9 = 17 - 2x

Then, we combine like terms if there any on both sides.

17 - 2x = 17 - 2x

Now, we can see the equations are equal to each other.

However, we can go a step further and solve for x.

17 - 2x = 17 - 2x

Subtract 17 from both sides.

-2x = -2x

Divide both sides by -2.

x = x

Therefore, x has no value or is 0.

User Cortright
by
5.3k points
3 votes

Answer: Infinite solutions

Explanation:


8-(2x-9)=17-2x

Begin by distributing the negative into the parenthesis.


8-2x+9=17-2x

Combine like terms;


17-2x=17-2x

Subtract 17


-2x=17-17-2x


-2x=-2x

Add 2x


-2x+2x=0\\0=0

User Digi
by
5.0k points